Determining the Effectiveness of Emotion-Focused Therapy on Psychological Well-being, Self-efficacy, and Happiness Among Lower Secondary School Female Students in Shiraz - Ghaffarian Javad, Farideh; Albehbahani, Marjan (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The purpose of this study is to identify the components and indicators influencing the selection process of textbook authors within Iran's educational system. Methods and Materials: Given the nature of the study, the research design is descriptive, and considering its objective, it is of an applied type. Methodologically, the study employed a survey approach. The statistical population consisted of experts, faculty members, and curriculum specialists involved in the selection of textbook authors. Data collection tools included interviews and questionnaires, and the fuzzy Delphi technique was applied. A total of 50 participants were selected using a non-random snowball sampling method. Findings: The results indicated that out of 18 identified components, 13 were considered significant based on a significance threshold of 8.94. These components included: teaching experience at various levels of the formal education system (9.35), participation in authorship, research, or prior curriculum planning (10.48), familiarity with learning psychology and instructional design principles (10.82), commitment to the Fundamental Reform Document of Education (9.36), familiarity with the National Curriculum (10.41), adherence to localization approaches (9.68), understanding of overarching educational goals (9.09), recognition of cultural and civilizational identity requirements (10.44), ability to simplify complex concepts (10.94), use of age-appropriate language (14.61), incorporation of practical examples and applications (11.90), proficiency in Persian writing style (11.36), and attention to students' individual differences (11.36). These components were deemed key factors in shaping the indicators for selecting textbook authors. Conclusion: Based on the analyzed dimensions and indicators, it can be concluded that the selection of textbook authors is not only a technical process but also a strategic issue that ensures educational quality, reinforces cultural identity, and aligns the education system with scientific advancements and contemporary societal needs. The results highlighted that the three dimensions—“academic expertise and teaching experience,” “alignment with policy documents,” and “educational writing ability”—interact synergistically to establish a framework capable of producing content that is scientific, localized, engaging, and learner-centered. Neglecting any of these dimensions or their associated indicators could result in textbooks that are scientifically weak, lack identity-building value, or fail to achieve educational effectiveness. Therefore, rethinking the policy-making and design of the author selection system is an urgent and strategic necessity for the future of national education.